2000
DOI: 10.1099/0022-1317-49-4-387
|View full text |Cite
|
Sign up to set email alerts
|

A method of decontaminating Strongyloides venezuelensis larvae for the study of strongyloidiasis in germ-free and conventional mice

Abstract: To study the possible in¯uence of intestinal micro-organisms on the course of strongyloidiasis in mice, a method was developed to obtain axenic infective larvae of Strongyloides venezuelensis. Cultured larvae from conventional mice were treated with sodium hypochlorite 0.25% for 10 min, washed in distilled water and then exposed to various combinations of antibiotics for 30 or 60 min. Success was achieved with a combination of penicillin 180 mg=L and ceftazidime 1 mg=ml. Decontamination of the larvae was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 2 publications
0
16
0
9
Order By: Relevance
“…Some nematodes have been successfully decontaminated and cultured in different media, although only a few reports have been published concerning the in vitro cultivation of parasites that belong to the genus Angiostrongylus (Hata 1996). In most studies, the decontamination of worms was achieved by incubation with several antibiotics or by gradient centrifugation, that may interfere with larval viability (Hata and Kojima 1991;Hata 1993Hata , 1994Hata , 1996Graeff-Teixeira et al 1999;Martins et al 2000). Furthermore, no confirmation of axenization has been demonstrated in a gnotobiotic model, except by Martins et al (2000).…”
Section: Treatmentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Some nematodes have been successfully decontaminated and cultured in different media, although only a few reports have been published concerning the in vitro cultivation of parasites that belong to the genus Angiostrongylus (Hata 1996). In most studies, the decontamination of worms was achieved by incubation with several antibiotics or by gradient centrifugation, that may interfere with larval viability (Hata and Kojima 1991;Hata 1993Hata , 1994Hata , 1996Graeff-Teixeira et al 1999;Martins et al 2000). Furthermore, no confirmation of axenization has been demonstrated in a gnotobiotic model, except by Martins et al (2000).…”
Section: Treatmentsmentioning
confidence: 95%
“…In most studies, the decontamination of worms was achieved by incubation with several antibiotics or by gradient centrifugation, that may interfere with larval viability (Hata and Kojima 1991;Hata 1993Hata , 1994Hata , 1996Graeff-Teixeira et al 1999;Martins et al 2000). Furthermore, no confirmation of axenization has been demonstrated in a gnotobiotic model, except by Martins et al (2000). The authors demonstrated by inoculation of germ-free mice that axenization of Strongyloides venezuelensis third-stage larvae is possible by the use of a 0.25% sodium hypochlorite wash, immediately followed by an antibiotic cocktail treatment for at least 30 min.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, it is well known that the presence of intestinal microbiota is essential for the pathogenicity of some protozoa and helminthes such as Entamoeba histolytica (Phillips & Wolfe, 1959), Nippostrongylus brasiliensis (Wescott & Todd, 1964), Nematospiroides dubius (Wescott, 1968), Trichinella spiralis (Przyjalkowski & Wescott, 1969), Eimeria tenella (Visco & Burns, 1972), Ascaridia galli (Johnson & Reid, 1973), Trichuris suis (Rutter & Beer, 1975), Eimeria falciformes (Owen, 1975), Eimeria ovinoidalis (Gouet et al, 1984) and Giardia duodenalis (Torres et al, 2000). In contrast, this microbiota can reduce the pathological consequences of other infectious diseases as described for experimental infections with Trypanosoma cruzi (Silva et al, 1987), Cryptococcus neoformans (Salkowski et al, 1987), Strongyloides venezuelensis (Martins et al, 2000) and almost all enteropathogenic bacteria (Clostridium difficile, Clostridium perfringens, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium, Shigella flexneri, Vibrio cholerae) (Wilson, 1995). Experimental infections with Raillietina cesticillus (Reid & Botero, 1967) and Isospora suis (Harleman & Meyer, 1984) are two of the very few cases where the normal microbiota has no influence on the course of a disease.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, the inbred AKR strain of mouse and its sublineages have been acquiring greater importance for evaluating the biology of intestinal nematodes 5,12,15,17,19,24,25,28,35 . However, studies on trematodes using the AKR strain remain scarce and address experimental infection using the species Brachylaima cribbi 6 , Schistosoma mansoni 4,15,27 and Zygocotyle lunata 2 .…”
mentioning
confidence: 99%